Práticas de leitura em inglês em ambiente digital e sua relação com o interesse e a participação de alunos de uma escola pública - Oliveira, Daniela Viana Araújo de (2008)
This research has begun from experiences with students of a public school in São Paulo. At the beginning, it was focused on the social and digital inclusion of those students through reading practices in English, in digital settings. Those practices have happened during computer mediated classes, in the computer laboratory of the school. However, many contextual factors make it impracticable to collect data through those practices, leading to change face-to-face settings to on-line ones. Changes in methodology and analysis were also necessary after that settings change. Thus, problems of different nature also came up, like the selection of participants, as an example. The objectives, then, have started to focus on the relationship between new reading practices in digital settings with interest and participation of students from that same school. Notwithstanding, the students selected as participants for the data collection were other students, different from those selected at the first moment. Many issues which needed to be reflected and worked upon the scope of education arose after those changes. The main issue is the need of specific preparation for teachers, in order to work with practices in digital settings. The data analysis revealed signs of better and more interest and participation of students within those new practices. Nevertheless, there is much to do in the public school: face old problems and work upon new proposals in order to guarantee a successful education